Oil Price, Budget Deficit, Money Supply and Inflation in WAEMU Countries - Hervé, DRAMA Bedi Guy; Ange-Patrick, Yao Kouadio (Asian Journal of Economic Modelling, 2018)
The main target of this paper is to explore both in short and long run the effects of world oil price, budget deficit and money growth on inflation in West African Economic and Monetary Union (WAEMU) running the period of 1990 to 2016. In that end, we utilized the autoregressive distributed lag (ARDL) bounds test approach developed by Pesaran et al. (2001) and the granger causality test. The empirical investigation indicates strong evidence of long run relationship among variables in all countries covered by the study except Togo. Oil price and inflation are positively linked in a very large majority of the member countries. There is positive and significant relationship between budget deficit and price level in Burkina Faso and Niger. In addition, our empirical work supports strong evidence that monetary expansion is positively linked with price level in Burkina Faso, Mali and Togo. In short run, the Granger causality demonstrated that budget deficit doesn’t cause money growth in WAEMU countries. It should be mentioned that the oil price has not an impact on inflation in all countries at short term. So, the main finding of this study is that oil price drives up inflation in the WAEMU zone in long term, but not in short time. As policy implication, the study suggests, among others, some improvements in growth policy, trade policy, general tax policy, raw material production, fuel efficiency and diversity.